Correlation between Maximal Inspiratory Pressure and the Sit-to-Stand Test in Post-COVID-19 Patients - Siti Chandra Widjanantie; Erick Ary Tjawanta; Triya Damayanti; Cleopas Martin Rumende; Andari Perwira Putri; Heidy Agustin; Erna Setiawati; Sri Wahyudati (RSUP Dr. Kariadi, 2025)
BACKGROUND: Coronavirus Disease 2019 (COVID-19) can lead to long-lasting complications such as ongoing respiratory issues and functional impairments. Damage to the alveoli and respiratory muscles, particularly the diaphragm, may result in lower maximal inspiratory pressure (MIP) and decreased physical performance. Although prior studies have examined the connection between MIP and functional tests in various respiratory conditions, research focusing on post-COVID-19 populations, particularly in Indonesia, is scarce. AIMS: To investigate the correlation between Maximal Inspiratory Pressure (MIP) and 30-second Sit-to-Stand (30s STS) test performance in adult post-COVID-19 patients. METHOD: A cross-sectional study was conducted at two tertiary hospitals in Jakarta, Indonesia, involving 40 adults post-COVID-19 patients aged 18–59 years. Participants underwent clinical screening, spirometry, MIP measurement using the MicroRPM device, and the 30s STS test. Pearson correlation analysis was used for normally distributed variables with significance set at p < 0.05. RESULT: The average MIP was 79.03 ± 26.68 cmH₂O, while the mean score for the 30s STS test was 12.78 ± 2.47 repetitions. Spirometric measurements revealed an average FEV₁ of 2.23 ± 0.57 L, FVC of 2.84 ± 0.69 L, and an FEV₁/FVC ratio of 81.19%. A moderate positive correlation between MIP and 30s STS performance was identified (r = 0.515, p = 0.001). CONCLUSION: There is a significant moderate correlation between MIP and 30s STS performance among post-COVID-19 patients, suggesting that simple functional tests can be effective tools for assessing respiratory muscle strength and informing rehabilitation strategies in clinical environments.